2010
DOI: 10.1063/1.3297879
|View full text |Cite
|
Sign up to set email alerts
|

Spin-transfer switching in an epitaxial spin-valve nanopillar with a full-Heusler Co2FeAl0.5Si0.5 alloy

Abstract: We report magnetization switching by spin-transfer torque in an epitaxial spin-valve nanopillar made with a half-metallic full-Heusler Co2FeAl0.5Si0.5 (CFAS) alloy. The CFAS/Ag/CFAS spin valves showed a magnetoresistance ratio of 7%–9%, and spin-transfer switching was clearly observed in the nanopillar by applying a relatively small dc current (∼106 A/cm2 in current density). Statistical analysis based on a thermal activation model revealed an averaged critical current density (Jc0) of 9.3×106 A/cm2 with a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Furubayashi et al 15 found a large magnetoresistance ratio of 6.9% at room temperature (RT) for Co 2 FeAl 0.5 Si 0.5 (CFAS)/ Ag/CFAS spin-valves. Sukegawa et al 16 showed that the resistance-current curves of Co 2 FeAl 0.5 Si 0.5 spin-valves exhibited a two-step switching process, which is similar to the behavior of the Fe/Ag/Fe nanopillar 17 and originated from the interplay between the magnetocrystalline anisotropy of CFAS layers and STT. Unlike most cases, for both Co 2 FeAl 0.5 Si 0.5 and Fe/Ag/Fe spin-valves it is believed that there exists an intermediate (I) state, besides the parallel (P) and antiparallel (AP) spin configurations, with the direction of the spins perpendicular to their original and final states when an appropriate negative current is applied.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Furubayashi et al 15 found a large magnetoresistance ratio of 6.9% at room temperature (RT) for Co 2 FeAl 0.5 Si 0.5 (CFAS)/ Ag/CFAS spin-valves. Sukegawa et al 16 showed that the resistance-current curves of Co 2 FeAl 0.5 Si 0.5 spin-valves exhibited a two-step switching process, which is similar to the behavior of the Fe/Ag/Fe nanopillar 17 and originated from the interplay between the magnetocrystalline anisotropy of CFAS layers and STT. Unlike most cases, for both Co 2 FeAl 0.5 Si 0.5 and Fe/Ag/Fe spin-valves it is believed that there exists an intermediate (I) state, besides the parallel (P) and antiparallel (AP) spin configurations, with the direction of the spins perpendicular to their original and final states when an appropriate negative current is applied.…”
Section: Introductionmentioning
confidence: 93%
“…1, we studied a spin-valve device with geometry similar to the structure of the spin-valve in Ref. 16 [CFAS (20 nm)/Ag (4 nm)/CFAS (2.5 nm) of elliptical cross-section area (250 Â 190 nm 2 )]. We employ a Cartesian coordinate system where the x-axis is the long axis of the ellipse along the CFAS [110] direction (easy axis) and the y-axis is along the short axis ([1 dynamics are described using a generalized Landau-LifshitzGilbert-Slonczewski (LLGS) equation, 1,2 which can be written as…”
Section: Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations